Preparation method and application of nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel composites
The carbon quantum dot-anchored cobalt-nickel bimetal sulfide/graphene aerogel composite material is prepared through nitrogen and sulfur co-doping technology and directional refrigeration technology, which solves the problem of volume expansion and agglomeration of transition metal sulfide materials during charging and discharging, and realizes the preparation of high-performance supercapacitor electrode materials, with good cycling stability and high specific capacitance.
Patent Information
- Application Number
- CN202211686177.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The existing transition metal sulfide supercapacitor materials expand and agglomerate during charging and discharging, resulting in poor cycle stability, limiting their large-scale industrialization development. At the same time, graphene aerogel materials are easily stacked due to electrostatic interactions during assembly, resulting in uneven pores and low mechanical strength, and limited application.
Carbon quantum dot-anchored cobalt-nickel bimetallic sulfide/graphene aerogel composite material is prepared through nitrogen and sulfur co-doping technology, and the agglomeration problem between graphene sheets is solved by directed refrigeration technology, forming a uniform spatial distribution, and forming a tight interface interaction during carbonization and sulfur doping to avoid agglomeration of metal sulfide nanoparticles.
The high performance of supercapacitor electrode material is achieved, with good reversible charge and discharge capacity and excellent cycle stability, the specific capacitance can reach 2260~2390F/g, and the specific capacity retention rate after 1000 cycles is 88.1~90.8%.
Smart Images

Figure CN116190113B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to a preparation method and application of a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material. Background Art
[0002] As the key energy storage system for the next generation of smart wearable electronic devices, flexible solid-state supercapacitors have attracted more and more attention in the fields of flexible, lightweight, smart wearable energy storage devices, and biomedicine, and have very broad market potential. The energy storage mechanism of supercapacitors is divided into two types: double-layer energy storage and pseudocapacitor energy storage. Energy storage is mainly achieved by reversible chemical adsorption-desorption or oxidation-reduction reactions on the surface of electrode materials. Its storage performance is mainly determined by the type of electrode material, specific surface area, and oxidation-reduction ability. Transition metal sulfides, especially nanostructured transition bimetallic (oxygen) sulfides, are the most studied pseudocapacitor energy storage materials due to their high theoretical specific capacity. However, transition metal sulfides still have many problems, such as volume expansion and agglomeration during charging and discharging, which causes the active material to fall off or pulverize from the electrode sheet, resulting in a high irreversible capacity loss, resulting in poor cycle stability, and limiting the large-scale industrial development of transition metal sulfides.
[0003] At present, flexible supercapacitor electrodes generally use active materials constructed on the surface of metal mesh current collectors, conductive fabrics, carbon paper, polymers and other materials. However, due to the problems of heavy weight, low specific surface area and conductivity of these substrates, the improvement of supercapacitor energy density and power density is affected.
[0004] Graphene aerogel is a three-dimensional porous material constructed with graphene oxide as the assembly unit. It can be used as an ideal carrier for nanoparticles, nanowires, nanosheets, etc. due to its rich pores, large specific surface area, excellent conductivity, strong adsorption capacity, stable physical and chemical properties, etc. In recent years, it has been widely used in cutting-edge scientific and technological fields such as energy storage, catalysis, and environmental remediation. Graphene aerogels loaded with transition metal oxides / sulfur / hydroxides and conductive polymers are used as electrode materials, which can not only achieve good dispersion of nanoparticles but also improve their electrochemical properties. However, due to the large specific surface area of graphene, the electrostatic interaction between the sheets during the assembly process makes it easy to stack, resulting in uneven pores in the internal structure of the prepared aerogel, low mechanical strength, and high brittleness. At the same time, the low density of graphene aerogel is not suitable for high volume performance supercapacitor electrode materials. Therefore, the preparation of graphene aerogel-loaded transition metal sulfide materials is still challenging. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, which solves the problem of low mechanical strength and limited application of graphene aerogel caused by agglomeration between graphene nanosheets due to strong π-π interaction through directional freezing. After nitrogen and sulfur doping, the in-situ formed cobalt-nickel bimetallic sulfide active particles are tightly anchored on the graphene sheets and embedded in the aerogel three-dimensional network structure, forming a strong interface interaction, effectively avoiding the agglomeration problem between metal sulfide nanoparticles, making full use of the excellent electron transmission capacity of carbon quantum dots and graphene, forming a fast transmission path for ions and electrons during the charge and discharge process, and becoming an ideal high-performance supercapacitor electrode material.
[0006] The present invention is specifically implemented by the following technical scheme. According to the preparation method of a nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material proposed by the present invention, the method specifically comprises the following steps:
[0007] (1) adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate into deionized water and stirring to dissolve them to obtain a cobalt-nickel bimetallic salt solution A;
[0008] (2) adding a certain amount of sodium alginate to the graphene oxide solution and stirring for 5 to 8 hours to obtain solution B;
[0009] (3) slowly adding the solution A obtained in step (1) into the solution B obtained in step (2), stirring with a magnetic force for 4 to 8 hours, adjusting the pH value of the solution to alkaline with aqueous ammonia, and continuing stirring for 3 to 6 hours to obtain a suspension C;
[0010] (4) pouring the suspension C obtained in step (3) into a silica gel mold, and then placing it on the surface of a copper block immersed in liquid nitrogen at the bottom for directional freezing, and then freeze-drying it at a temperature of -50°C and a pressure of 10Pa for 48 hours to obtain a sodium alginate / cobalt nickel double metal hydroxide / graphene oxide composite aerogel;
[0011] (5) placing the sodium alginate / cobalt nickel bimetallic hydroxide / graphene oxide composite aerogel obtained in step (4) in a tubular furnace, evacuating the vacuum, and heating to 200-500° C. in an inert atmosphere for 2-4 hours for carbonization to obtain a carbon quantum dot-anchored cobalt nickel bimetallic oxide / graphene aerogel composite material;
[0012] (6) The carbon quantum dot-anchored cobalt nickel bimetallic oxide / graphene aerogel composite material obtained in step (5) is placed in a porcelain boat with a sulfur-doped reagent at the bottom and placed in a tubular furnace. After evacuation, the temperature is raised to 600-800° C. in an ammonia atmosphere and maintained for 2-4 hours to obtain a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt nickel bimetallic sulfide / graphene aerogel composite material.
[0013] In the preparation method of the aforementioned nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, the molar ratio of cobalt nitrate hexahydrate to nickel nitrate hexahydrate in step (1) is 2:1.
[0014] The preparation method of the aforementioned nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, in step (1), the concentration of cobalt nitrate in solution A is 0.1-0.8 mol / L, and the concentration of nickel nitrate is 0.05-0.4 mol / L.
[0015] In the preparation method of the aforementioned nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, the concentration of the graphene oxide solution in step (2) is 6 to 20 mg / mL, and the concentration of sodium alginate in solution B is 1 to 10 mg / mL.
[0016] In the aforementioned method for preparing the nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, the time for directional freezing in step (4) is 20 to 60 minutes.
[0017] In the preparation method of the aforementioned nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, the heating rate of step (5) is 5°C / min, and the heating rate of step (6) is 2°C / min.
[0018] The present invention also provides a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material and the use of the composite material in a supercapacitor electrode material. The composite material is obtained according to the aforementioned preparation method. When used as a supercapacitor electrode material, the specific capacitance thereof is 2260 to 2390 F / g. At a current density of 5 A / g, the retention rate of the specific capacitance thereof after 1000 cycles is 88.1 to 90.8%.
[0019] Compared with the prior art, the present invention has obvious advantages and beneficial effects, can achieve considerable technical progress and practicality, and has a wide range of use value. It has at least the following advantages:
[0020] (1) The present invention pairs cobalt and nickel metal ions with the carboxyl and hydroxyl groups of the G monomers on the sodium alginate molecular chain. 2+ and Ni 2+The ions are combined due to the electrostatic interaction between the negative charges of carboxyl and hydroxyl groups on the graphene oxide sheets, and the cobalt-nickel double hydroxide generated under alkaline conditions is loaded on the alginate molecular chain and the graphene oxide sheets. The ice template produced by directional freezing is used to achieve a uniform spatial distribution of graphene sheets and cobalt-nickel double hydroxide, which solves the problem of agglomeration caused by the strong π-π interaction between graphene nanosheets during the preparation of graphene aerogels, resulting in uneven pores, low mechanical strength, and limited application.
[0021] (2) In the preparation method of the present invention, during the carbonization process, the carbon quantum dots formed by the decomposition of sodium alginate are anchored on the cobalt-nickel bimetallic oxide converted from the cobalt-nickel bimetallic hydroxide after dehydration and are jointly loaded on the graphene sheet. In the subsequent nitrogen-sulfur doping process, the in-situ formed cobalt-nickel bimetallic sulfide active particles are tightly anchored on the graphene sheet and embedded in the three-dimensional network structure of the aerogel, forming a strong interface interaction. This can not only effectively avoid the agglomeration problem between the metal sulfide nanoparticles, but also provide a large specific surface area and space for buffering volume expansion. In addition, the excellent electron transmission ability of carbon quantum dots and graphene can be fully utilized to form a rapid transmission path for ions and electrons during the charge and discharge process, thereby becoming an ideal high-performance supercapacitor electrode material.
[0022] (3) The preparation method of the present invention is different from the traditional hydrothermal method for preparing graphene aerogel and cobalt-nickel bimetallic sulfide materials, and has the advantages of being simple in preparation method, easy to operate and scale up. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a digital photo of the nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material prepared in Example 1.
[0024] Figure 2 This is a scanning electron micrograph (SEM) of the nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel prepared in Example 1. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] (1) adding 0.582 g of cobalt nitrate hexahydrate and 0.291 g of nickel nitrate hexahydrate into 10 mL of deionized water and stirring to dissolve the mixture to obtain a cobalt-nickel bimetallic salt solution A;
[0028] (2) adding 80 mg of sodium alginate to 10 mL of 10 mg / mL graphene oxide solution and stirring for 5 h to obtain a graphene oxide-sodium alginate mixed solution B;
[0029] (3) Slowly adding the solution A obtained in step (1) into the solution B obtained in step (2), stirring by magnetic force for 6 hours, adjusting the pH value of the solution to 14 with aqueous ammonia, and continuing stirring for 4 hours to obtain a suspension C;
[0030] In this step, the cobalt-nickel bimetallic salt solution is slowly added to the sodium alginate-graphene oxide mixed solution, and the Co 2+ and Ni 2+ With Na in sodium alginate + Ion exchange occurs, and the carboxyl and hydroxyl groups on the adjacent alginate molecular chains G monomers are coordinated and fixed. 2+ and Ni 2+ The ions are bound due to the electrostatic interaction between them and the negative charges of the carboxyl and hydroxyl groups on the graphene oxide sheets. 2+ and Ni 2+ Ions and OH in solution - The cobalt-nickel double hydroxide generated by ion combination is loaded on the alginate molecular chain and the graphene oxide sheet to prepare the sodium alginate / cobalt-nickel double hydroxide / graphene oxide suspension C.
[0031] (4) Pour the suspension C obtained in step (3) into a 3×3×3 cm 3 The silicone mold was then placed on a copper block (5×5×5cm) immersed in liquid nitrogen at the bottom. 3 ) surface was subjected to directionally freezing for 30 min, and then freeze-dried at a temperature of -50°C and a pressure of 10 Pa for 48 h to obtain a sodium alginate / cobalt nickel double metal hydroxide / graphene oxide composite aerogel; liquid nitrogen was placed in a wide-mouth thermos bottle, and the height of the liquid nitrogen in the bottle was less than 4 cm.
[0032] This step utilizes the excellent thermal conductivity of the copper block to form a bottom-up temperature gradient from the bottom of the mold to the surface of the solution to directionally freeze the suspension C. The ice converted from water during the freezing process is used as a template to induce the directional arrangement of the graphene oxide sheets. After freeze-drying, an orderly arranged graphene composite aerogel is obtained, which can effectively solve the problem of poor mechanical properties caused by agglomeration of graphene sheets due to strong π-π interactions.
[0033] (5) The composite aerogel obtained in step (4) is placed in a tubular furnace, evacuated, and then carbonized in an inert atmosphere of argon at a heating rate of 5°C / min from room temperature to 500°C for 2 h.
[0034] During the carbonization process, the carbon quantum dots formed by the decomposition of sodium alginate are anchored on the cobalt-nickel bimetallic oxide converted from the cobalt and nickel bimetallic hydroxides after dehydration and are jointly loaded on the graphene sheets to obtain a carbon quantum dot-anchored cobalt-nickel bimetallic oxide / graphene aerogel composite material.
[0035] (6) The composite material obtained in step (5) is placed in a porcelain boat with sublimated sulfur at the bottom and placed in a tube furnace. After evacuation, the temperature is raised from room temperature to 600° C. at a rate of 2° C. / min in an ammonia atmosphere and maintained for 2 hours. At high temperature, ammonia is used as a nitrogen source and sulfur vapor is used as a sulfur source to form nitrogen-sulfur co-doped graphene sheets. At the same time, cobalt-nickel bimetallic oxide is in-situ converted into cobalt-nickel bimetallic sulfide, thereby obtaining a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material.
[0036] The cobalt-nickel bimetallic sulfide active particles formed in situ in this step are tightly anchored on the graphene sheets and embedded in the three-dimensional network structure of the aerogel, forming a strong interface interaction. This can not only effectively avoid the agglomeration problem between the metal sulfide nanoparticles, provide a large specific surface area and space for buffering volume expansion, but also make full use of the excellent electron transmission capabilities of carbon quantum dots and graphene to form a rapid transmission path for ions and electrons during the charging and discharging process, thus becoming an ideal high-performance supercapacitor electrode material.
[0037] The weighed nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material was used as an aerogel electrode, and activated carbon, polytetrafluoroethylene binder, and acetylene black conductive agent were mixed in a mass ratio of 8:1:1, and a small amount of ethanol was added to fully stir into a slurry, which was applied on the nickel foam and dried to make an activated carbon electrode. The aerogel electrode, activated carbon electrode, and cellulose diaphragm were immersed in polyvinyl alcohol / sulfuric acid gel electrolyte to fully absorb the electrolyte, and then assembled into a sandwich structure in the order of aerogel electrode, diaphragm, and activated carbon electrode and dried in the air, and then the aerogel electrode and activated carbon electrode were connected to a copper strip respectively and led out, and then sealed between two PET plastic films to prepare a flexible solid-state supercapacitor. Cyclic voltammetry and constant current charge and discharge tests were carried out on an electrochemical workstation. Calculations showed that when the prepared nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material is used as an electrode material for a supercapacitor, its specific capacitance can reach 2390F / g, and at a current density of 5A / g, after 1000 cycles, its specific capacity can still be retained at 88.1%, indicating that the prepared nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material has good reversible charge and discharge capacity and excellent cycle stability when used as a supercapacitor electrode material.
[0038] Figure 1 Shown is a digital photo of the nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material prepared in Example 1. As can be seen from the figure, the prepared aerogel has a regular shape.
[0039] Figure 2 Shown is a scanning electron micrograph (SEM) of the nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel prepared in Example 1. As can be seen from the figure, the prepared composite aerogel is a directional layered structure, so that it has good mechanical properties.
[0040] Example 2
[0041] (1) adding 1.164 g of cobalt nitrate hexahydrate and 0.582 g of nickel nitrate hexahydrate into 10 mL of deionized water and stirring to dissolve the mixture to obtain a cobalt-nickel bimetallic salt solution A;
[0042] (2) adding 50 mg of sodium alginate to 10 mL of 8 mg / mL graphene oxide solution, and continuing stirring for 8 h to obtain a graphene oxide-sodium alginate mixed solution B;
[0043] (3) slowly adding the mixed solution A obtained in step (1) into the mixed solution B obtained in step (2), stirring the mixture by magnetic force for 6 hours, adjusting the pH value of the solution to 11 with aqueous ammonia, and continuing stirring for 4 hours to obtain a suspension C;
[0044] In this step, the cobalt-nickel bimetallic salt solution is slowly added to the sodium alginate-graphene oxide mixed solution, and the Co 2+ and Ni 2+ With Na in sodium alginate + Ion exchange occurs, and the carboxyl and hydroxyl groups on the adjacent alginate molecular chains G monomers are coordinated and fixed. 2+ and Ni 2+ The ions are bound due to the electrostatic interaction between them and the negative charges of the carboxyl and hydroxyl groups on the graphene oxide sheets. 2+ and Ni 2+ Ions and OH in solution - The cobalt-nickel double hydroxide generated by ion combination is loaded on the alginate molecular chain and the graphene oxide sheet to prepare the sodium alginate / cobalt-nickel double hydroxide / graphene oxide suspension C.
[0045] (4) Pour the suspension C obtained in step (3) into a 3×3×3 cm 3 A copper block (5×5×5cm 3 ) surface was subjected to directionally freezing for 40 min, and then freeze-dried at a temperature of -50°C and a pressure of 10 Pa for 48 h to obtain a sodium alginate / cobalt nickel double metal hydroxide / graphene oxide composite aerogel; liquid nitrogen was placed in a wide-mouth thermos bottle, and the height of the liquid nitrogen in the bottle was less than 4 cm.
[0046] This step utilizes the excellent thermal conductivity of the copper block and the bottom-up temperature gradient formed from the bottom of the mold to the surface of the solution to directionally freeze the suspension C. The ice converted from water during the freezing process is used as a template to induce the directional arrangement of the graphene oxide sheets. After freeze-drying, an orderly arranged graphene composite aerogel is obtained, which can effectively solve the problem of poor mechanical properties caused by agglomeration of graphene sheets due to strong π-π interactions.
[0047] (5) The composite aerogel obtained in step (4) is placed in a tubular furnace, evacuated, and then carbonized in an inert atmosphere of argon at a heating rate of 5°C / min from room temperature to 400°C for 3 hours.
[0048] During the carbonization process, the carbon quantum dots formed by the decomposition of sodium alginate are anchored on the cobalt-nickel bimetallic oxide converted from the cobalt and nickel bimetallic hydroxides after dehydration and are jointly loaded on the graphene sheets to obtain a carbon quantum dot-anchored cobalt-nickel bimetallic oxide / graphene aerogel composite material.
[0049] (6) The composite material obtained in step (5) is placed in a porcelain boat with sublimated sulfur at the bottom and placed in a tube furnace. After evacuation, the temperature is raised from room temperature to 700° C. at a rate of 2° C. / min in an ammonia atmosphere and maintained for 2 hours. At high temperature, ammonia is used as a nitrogen source and sulfur vapor is used as a sulfur source to form nitrogen-sulfur co-doped graphene sheets. At the same time, cobalt-nickel bimetallic oxide is in-situ converted into cobalt-nickel bimetallic sulfide, thereby obtaining a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material.
[0050] The cobalt-nickel bimetallic sulfide active particles formed in situ in this step are tightly anchored on the graphene sheets and embedded in the three-dimensional network structure of the aerogel, forming a strong interface interaction. This can not only effectively avoid the agglomeration problem between the metal sulfide nanoparticles, provide a large specific surface area and space for buffering volume expansion, but also make full use of the excellent electron transmission capabilities of carbon quantum dots and graphene to form a rapid transmission path for ions and electrons during the charging and discharging process, thus becoming an ideal high-performance supercapacitor electrode material.
[0051] A nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material was used as an aerogel electrode and assembled into a flexible solid-state supercapacitor according to the same method as in Example 1. The electrode specific capacitance was tested to be 2280F / g, and at a current density of 5A / g, after 1000 cycles, its specific capacity could still retain 90.8%, showing good reversible charge and discharge capacity and excellent cycle stability.
[0052] Example 3
[0053] (1) adding 0.291 g of cobalt nitrate hexahydrate and 0.146 g of nickel nitrate hexahydrate into 10 mL of deionized water and stirring to dissolve the mixture to obtain a cobalt-nickel bimetallic salt solution A;
[0054] (2) adding 60 mg of sodium alginate to 10 mL of 15 mg / mL graphene oxide solution, and continuing stirring for 8 h to obtain a graphene oxide-sodium alginate mixed solution B;
[0055] (3) slowly adding the mixed solution A obtained in step (1) into the mixed solution B obtained in step (2), stirring the mixture by magnetic force for 6 hours, adjusting the pH value of the solution to 12 with aqueous ammonia, and continuing stirring for 4 hours to obtain a suspension C;
[0056] In this step, the cobalt-nickel bimetallic salt solution is slowly added to the sodium alginate-graphene oxide mixed solution, and the Co 2+ and Ni 2+ With Na in sodium alginate + Ion exchange occurs, and the carboxyl and hydroxyl groups on the adjacent alginate molecular chains G monomers are coordinated and fixed. 2+and Ni 2+ The ions are bound due to the electrostatic interaction between them and the negative charges of the carboxyl and hydroxyl groups on the graphene oxide sheets. 2+ and Ni 2+ Ions and OH in solution - The cobalt-nickel double hydroxide generated by ion combination is loaded on the alginate molecular chain and the graphene oxide sheet to prepare the sodium alginate / cobalt-nickel double hydroxide / graphene oxide suspension C.
[0057] (4) Pour the suspension C obtained in step (3) into a 3×3×3 cm 3 A copper block (5×5×5cm 3 ) surface was subjected to directionally freezing for 50 min, and then freeze-dried at a temperature of -50°C and a pressure of 10 Pa for 48 h to obtain a sodium alginate / cobalt nickel double metal hydroxide / graphene oxide composite aerogel; liquid nitrogen was placed in a wide-mouth thermos bottle, and the height of the liquid nitrogen in the bottle was less than 4 cm.
[0058] This step utilizes the excellent thermal conductivity of the copper block and the bottom-up temperature gradient formed from the bottom of the mold to the surface of the solution to directionally freeze the suspension C. The ice converted from water during the freezing process is used as a template to induce the directional arrangement of the graphene oxide sheets. After freeze-drying, an orderly arranged graphene composite aerogel is obtained, which can effectively solve the problem of poor mechanical properties caused by agglomeration of graphene sheets due to strong π-π interactions.
[0059] (5) The composite aerogel obtained in step (4) is placed in a tubular furnace, evacuated, and then carbonized in an inert atmosphere of argon at a heating rate of 5°C / min from room temperature to 450°C for 2 h.
[0060] During the carbonization process, the carbon quantum dots formed by the decomposition of sodium alginate are anchored on the cobalt-nickel bimetallic oxide converted from the cobalt and nickel bimetallic hydroxides after dehydration and are jointly loaded on the graphene sheets to obtain a carbon quantum dot-anchored cobalt-nickel bimetallic oxide / graphene aerogel composite material.
[0061] (6) The composite material obtained in step (5) is placed in a porcelain boat with sublimated sulfur at the bottom and placed in a tube furnace. After evacuation, the temperature is raised from room temperature to 800° C. at a heating rate of 2° C. / min in an ammonia atmosphere and maintained for 4 hours. At high temperature, ammonia is used as a nitrogen source and sulfur vapor is used as a sulfur source to form nitrogen-sulfur co-doped graphene sheets. At the same time, cobalt-nickel bimetallic oxide is in-situ converted into cobalt-nickel bimetallic sulfide, thereby obtaining a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material.
[0062] The cobalt-nickel bimetallic sulfide active particles formed in situ in this step are tightly anchored on the graphene sheets and embedded in the three-dimensional network structure of the aerogel, forming a strong interface interaction. This can not only effectively avoid the agglomeration problem between the metal sulfide nanoparticles, provide a large specific surface area and space for buffering volume expansion, but also make full use of the excellent electron transmission capabilities of carbon quantum dots and graphene to form a rapid transmission path for ions and electrons during the charging and discharging process, thus becoming an ideal high-performance supercapacitor electrode material.
[0063] A nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material was used as an aerogel electrode and assembled into a flexible solid-state supercapacitor according to the same method as in Example 1. After testing, the electrode specific capacitance could reach 2260F / g, and at a current density of 5A / g, its specific capacity could still retain 88.7% after 1000 cycles, showing good reversible charge and discharge capacity and excellent cycle stability.
[0064] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material, characterized in that The following steps are involved: (1) adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate into deionized water, stirring and dissolving them, thereby obtaining a cobalt-nickel bimetallic salt solution A; (2) Add a certain amount of sodium alginate to the graphene oxide solution and stir for 5 to 8 hours to obtain solution B; (3) Slowly adding the solution A obtained in step (1) into the solution B obtained in step (2), stirring with a magnetic force for 4 to 8 hours, adjusting the pH value of the solution to alkaline with aqueous ammonia, and continuing stirring for 3 to 6 hours to obtain a suspension C; (4) pouring the suspension C obtained in step (3) into a silica gel mold, and then placing it on the surface of a copper block immersed in liquid nitrogen at the bottom for directional freezing, and then freeze-drying it at a temperature of -50°C and a pressure of 10Pa for 48 hours to obtain a sodium alginate / cobalt nickel double metal hydroxide / graphene oxide composite aerogel; (5) placing the sodium alginate / cobalt nickel bimetallic hydroxide / graphene oxide composite aerogel obtained in step (4) in a tubular furnace, evacuating the vacuum, and then heating the furnace to 200-500° C. in an inert atmosphere for 2-4 hours for carbonization to obtain a carbon quantum dot-anchored cobalt nickel bimetallic oxide / graphene aerogel composite material; (6) The carbon quantum dot-anchored cobalt nickel bimetallic oxide / graphene aerogel composite material obtained in step (5) is placed in a porcelain boat with a sulfur-doped reagent at the bottom and placed in a tubular furnace. After evacuation, the temperature is raised to 600-800° C. in an ammonia atmosphere and maintained for 2-4 hours to obtain a nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt nickel bimetallic sulfide / graphene aerogel composite material.
2. The method for preparing the nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material according to claim 1, characterized in that In step (1), the molar ratio of cobalt nitrate hexahydrate to nickel nitrate hexahydrate is 2:
1.
3. The method for preparing the nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material according to claim 1, characterized in that In step (1), the concentration of cobalt nitrate in solution A is 0.1-0.8 mol / L, and the concentration of nickel nitrate is 0.05-0.4 mol / L.
4. The method for preparing the nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material according to claim 1, characterized in that The concentration of the graphene oxide solution in step (2) is 6 to 20 mg / mL, and the concentration of the sodium alginate in solution B is 1 to 10 mg / mL.
5. The method for preparing the nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material according to claim 1, characterized in that The time of directional freezing in step (4) is 20 to 60 minutes.
6. The method for preparing the nitrogen-sulfur co-doped carbon quantum dot anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material according to claim 1, characterized in that The heating rate of step (5) is 5°C / min, and the heating rate of step (6) is 2°C / min.
7. A nitrogen-sulfur co-doped carbon quantum dot-anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the nitrogen-sulfur co-doped carbon quantum dots anchored cobalt-nickel bimetallic sulfide / graphene aerogel composite material as claimed in claim 7 in supercapacitor electrode materials.
Citation Information
Patent Citations
Graphene aerogel loaded two-phase transition metal sulfide as well as preparation method and application thereof
CN106328947A
Carbon quantum dots / reduced graphene oxide composite gel, and preparation method and application of same
CN107601464A